Public investment, the rate of return, and optimal fiscal policy - Arrow, Kenneth J.; Kurz, Mordecai; Resources for the Future (Baltimore : Published for Resources for the Future by the Johns Hopkins Press, 1970)
This book, co-authored by the Nobel-prized economist, Kenneth Arrow, considers public expenditures in the context of modern growth theory. It analyzes optimal growth with public capital. A theory of 'controllability' is developed and injected into public economics and growth models.
Bibliography: p. 209-213.
uaa 22/01/19
Loans
Keywords: Expenditures, Public; Government spending policy; Fiscal policy; Economic policy